The role of epigenetic and epitranscriptomic modifications in plants exposed to non-essential metals - Chmielowska-Bąk, Jagna; Searle, Iain Robert; Wakai, Theophilus Nang; Arasimowicz-Jelonek, Magdalena (Frontiers in Plant Science, 2023)
Contamination of the soil with non-essential metals and metalloids is a serious problem in many regions of the world. These non-essential metals and metalloids are toxic to all organisms impacting crop yields and human health. Crop plants exposed to high concentrations of these metals leads to perturbed mineral homeostasis, decreased photosynthesis efficiency, inhibited cell division, oxidative stress, genotoxic effects and subsequently hampered growth.Plants can activate epigenetic and epitranscriptomic mechanisms to maintain cellular and organism homeostasis. Epigenetic modifications include changes in the patterns of cytosine and adenine DNA base modifications, changes in cellular non-coding RNAs, and remodelling histone variants and covalent histone tail modifications. Some of these epigenetic changes have been shown to be longlasting and may therefore contribute to stress memory and modulated stress tolerance in the progeny.In the emerging field of epitranscriptomics, defined as chemical, covalent modifications of ribonucleotides in cellular transcripts, epitranscriptomic modifications are postulated as more rapid modulators of gene expression.Although significant progress has been made in understanding the plant's epigenetic changes in response to biotic and abiotic stresses, a comprehensive review of the plant's epigenetic responses to metals is lacking. While the role of epitranscriptomics during plant developmental processes and stress responses are emerging, epitranscriptomic modifications in response to metals has not been reviewed. This article describes the impact of non-essential metals and metalloids (Cd, Pb, Hg, Al and As) on global and site-specific DNA methylation, histone tail modifications and epitranscriptomic modifications in plants.